Targeted Single Wall Carbon Nanotube Mediated Pt(IV) Prodrug Delivery Using Folate as a Homing Device - Dhar, Shanta (2008)
Most low molecular weight platinum anticancer drugs have short blood circulation times that are reflected in their reduced tumor uptake and intracellular DNA binding. A platinum(IV) complex of the formula c,c,t-[Pt(NH(3))(2)Cl(2)(O(2)CCH(2)CH(2)CO(2)H)(O(2)CCH(2)CH(2)CONH-PEG-FA)] (1) containing a folate derivative (FA) at an axial position was prepared and characterized. Folic acid offers a means of targeting human cells that highly overexpress the folate receptor (FR). Compound 1 was attached to the surface of an amine functionalized single walled carbon nanotube (SWNT-PL-PEG-NH(2)) through multiple amide linkages to use the SWNTs as a “longboat delivery system” for the platinum warhead, carrying it to the tumor cell and releasing cisplatin upon intracellular reduction of Pt(IV) to Pt(II). The ability of SWNT tethered 1 to destroy selectively FR(+) vs FR(−) cells demonstrated its ability to target tumor cells that overexpress the FR on their surface. That the SWNTs deliver the folate-bearing Pt(IV) cargos into FR(+) cancer cells by endocytosis was demonstrated by the localization of fluorophorelabeled SWNTs using fluorescence microscopy. Once inside the cell, cisplatin formed upon reductive release from the longboat oars enters the nucleus and reacts with its target nuclear DNA, as determined by platinum atomic absorption spectroscopy of cell extracts. Formation of the major cisplatin 1,2-intrastrand d(GpG) cross-links on the nuclear DNA was demonstrated by use of a monoclonal antibody specific for this adduct. The SWNT-tethered compound 1 is the first construct in which both targeting and delivery have been incorporated into the same molecule; it is also the first demonstration that intracellular reduction of a Pt(IV) pro-drug leads to the cis-{Pt((NH(3))(2)} 1,2-intrastrand d(GpG) crosslink in nuclear DNA.